The Relevance of Acculturation in the Use of New Media for Public Information Disclosure in Islamic Communication Education Strategies (The Relationship between Religion, Science, and Technology) - Fitria, Nurul Jannah Lailatul; Aprilyandi, Ferdy; Adinda, Shanty Bunga (Indonesian Journal of Islamic Educational Review, 2025)
The current information age encompasses all aspects of human life. Media for communication and information dissemination has developed gradually and rapidly. Information media began with print and electronic media, and has now evolved into new media. The modern form of information openness using new media is not actually contrary to Islam. Islamic law also regulates and guides Muslims not to isolate themselves from the progress of the times. This is an interesting topic to explore further regarding public information transparency through new media in relation to Islamic teachings on ethics in Islamic communication. This research adopts a descriptive qualitative approach. This literature review is structured descriptively using secondary data from previous studies conducted by other researchers. The results of the study indicate that public information disclosure through new media is relevant to Islamic teachings on Islamic communication ethics. The timeliness of information in new media is consistent with Islamic teachings on avoiding hate speech based on differences. The completeness of information in new media is consistent with the principles of communication and language use based on values of goodness. The reliability of information in new media is in line with the principles of communication regarding truth and patience. The accuracy of information in new media is in line with the principles of Islamic communication with filtering in receiving information (tabayyun).